Effects of Electroporation on Biological Membranes Exposed to High Potentials - Nhung, Nguyen Thi Thuy; Tung, Le Thanh; Giang, Nguyen Duc; Thanh, Ngo Van; Viet, Nguyen Ai (Communications in Physics, 2012)
This study first considers that voltages of cellular organelle membranes could significanly surpass these of plasma membranes under the influence of ultrashort and high-intensity electric pulse. This is due to the voltages induced on the membrane. Using an approximate theory coordinated with the Kotnik’s analytical method, considering the electroporation, we focus on the reactions of cell membranes placed in a trapezoidal pulse. Then, we discuss conductive power dissipations of normal cell and cancer cell generated by a sinusoidal exposure which include dielectric relaxation effects. In comparison with the complex numerical calculations of Joshi et al, our results are in very good agreement.